2016
DOI: 10.1057/s41262-016-0021-5
|View full text |Cite
|
Sign up to set email alerts
|

Journal of Brand Management – Year end review 2016

Abstract: A review and reflection on key topics plus extrapolation of future research avenues from within the Journal of Brand Management during 2016 that included a special issue focused on the themes of (i) Corporate identity, branding, marketing, communication, and reputation. Seven additional themes within the Volume are identified: (ii) Brand engagement, (iii) Brand orientation, (iv) Brand counterfeiting and protection, (v) Online and digital branding, (vi) Brand and product naming, (vii) City branding, and (viii) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…We observed that despite the concept of corporate brand orientation is one of the extensions of brand orientation (Anees-ur-Rehman et al , 2016; Balmer, 2013) this keyword (corporate brand orientation) is not widely used in the articles. On the other hand, corporate brand and corporate branding are the terms most frequently used (Powell, 2016) and appear in this study’s sample.…”
Section: Results Of Bibliometric Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…We observed that despite the concept of corporate brand orientation is one of the extensions of brand orientation (Anees-ur-Rehman et al , 2016; Balmer, 2013) this keyword (corporate brand orientation) is not widely used in the articles. On the other hand, corporate brand and corporate branding are the terms most frequently used (Powell, 2016) and appear in this study’s sample.…”
Section: Results Of Bibliometric Analysismentioning
confidence: 97%
“…Moreover, within the mix of characteristics that a certain segment can present, putting together, for example, small and medium-sized B2B and B2C companies from different countries with different strategies, the multi-group analysis can be a powerful tool to analyse these distinctions, as in the study by Reijonen et al (2015). In addition, Boso et al (2016) suggest research in the BRICS countries (Brazil, Russia, China, India and South Africa) and MINT (Mexico, Indonesia, Nigeria and Turkey) and studies that compare the results for both developed and developing economies (Powell, 2016).…”
Section: Research Agendamentioning
confidence: 99%
“…As noted in the above Special Issue and evidenced in previous Volumes of the Journal of Brand Management (Powell 2016), online and digital branding continues to attract increased attention from researchers and practitioners. (Bıçakcıoglu et al 2017) Refining the conceptualization of Brand Authenticity (Akbar and Wymer 2017) Brand value, accounting standards, and mergers and acquisitions: ''The Moribund Effect'' (Sinclair and Keller 2017) Isolating strategy effectiveness of brands in an emerging market: a choice modeling approach (Ghose et al 2017) Music and its multitude of meanings: exploring what makes brand placements in music videos authentic (Burkhalter et al 2017) Planning pre-launch positioning: segmentation via willingness-topay and means-end brand differentiators (Gengler and Mulvey 2017) The future of brand protection: responding to the global risk (Wilson 2017) Consumer-brand identification revisited: an integrative framework of brand identification, customer satisfaction, and price image and their role for brand loyalty and word of mouth (Popp and Woratschek 2017) A tale of two brands: the joint effect of manufacturer and retailer brands on consumers' product evaluation (Zhu and Chen 2017) Measuring farmer's satisfaction and brand loyalty toward Indian fertilizer brands using DEA (Mohanty and Senthil Kumar 2017) Global brand value in developed, emerging, and least developed country markets (Randrianasolo 2017) New brand logo design: customers' preference for brand name and icon (Bresciani and Del Ponte 2017) Self-congruence is not everything for a brand: initial evidence supporting the relevance of identity cultivation in a college student role-identity context (Ewing and Allen 2017) Brand network communities: leveraging brand relationships within the supply-chain (Hawkins 2017) The impact of atypical product design on consumer product and brand perception (Schnurr 2017) Pinto and Yagnik (2017) present an interesting study on the use of Facebook in social media marketing by fitness tracker brands (Fitbit, Garmin Fitness, Jawbone, and Misfit).…”
Section: Online and Digital Brandingmentioning
confidence: 86%
“…End-of-year reviews were provided at the conclusion of Volume 22 and 23 reflecting on their contents (Powell 2015(Powell , 2016. As Volume 24 draws to a close, we would like to review again some of the latest research on branding.…”
Section: Introductionmentioning
confidence: 99%
“…Consumer brand engagement is often conceptualized as a psychological state that is distinct to behavioral manifestations (France et al 2016 ). Research has tended to approach brand engagement from a firm perspective and has indicated that organizational offerings and marketing promotions affect consumer brand engagement (De Vries and Carlson 2014 ; Powell 2016 ; Whelan and Wohlfeil 2006 ). However, the concept of engagement is often reflective of an interactive connection with an object (Brodie et al 2011 ).…”
Section: Literature Reviewmentioning
confidence: 99%